2023
DOI: 10.29333/iji.2023.16230a
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Indonesian Instructional Books with a Scientific Approach on Students’ Learning Outcomes in Scientific Writing

Abstract: This study aims to investigate the influence of Indonesian instructional books with a scientific approach on students' learning outcomes in scientific writing viewed from their academic ability. This is quasi-experimental research design. Techniques used to collect data were tests in form of multiple choice and essay, observations, and documentations. Before conducting t-test, the researchers conducted a prerequisite test. Its results for the influence of Indonesian instructional books with a scientific approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(71 reference statements)
0
0
0
Order By: Relevance
“…The results of this study are in line with the findings of Suprihatin et al (2023) who concluded that the development of moral assessment can be integrated into subjects with the aim that students are able to use knowledge, study, and internalize values and social skills to develop noble character which is manifested in daily behavior. Harmawati, Sapriya, & Bestari (2022) also found the same thing that evaluating noble morals is a way of building character.…”
Section: (A) Moral Assessmentsupporting
confidence: 88%
“…The results of this study are in line with the findings of Suprihatin et al (2023) who concluded that the development of moral assessment can be integrated into subjects with the aim that students are able to use knowledge, study, and internalize values and social skills to develop noble character which is manifested in daily behavior. Harmawati, Sapriya, & Bestari (2022) also found the same thing that evaluating noble morals is a way of building character.…”
Section: (A) Moral Assessmentsupporting
confidence: 88%
“…One exception, with some limitations, may be Rustipa et al (2023), who concentrated on tenses choices and rhetorical patterns of unpublished scientific articles. Aspects of scientific writing were also followed by Suprihatin et al (2023), but attention was paid to instructional textbooks here. Some previous studies focused on texts with general topics, e.g.…”
Section: Publishers´ Requirementsmentioning
confidence: 99%